2010
DOI: 10.1088/0953-4075/43/5/055201
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of electrons from acetaldehyde and acetone

Abstract: Absolute total cross sections (TCSs) for electron scattering from acetaldehyde [(CH 3)CHO] and acetone [(CH 3) 2 CO] molecules have been measured at electron-impact energy extending from 0.7 to 400 eV, using a linear electron-transmission technique. The shape of obtained TCS energy dependences appears typical for targets of high electric dipole moment; both TCSs decrease with the energy increase; only between 4 and 12 eV is a weak enhancement in TCSs is clearly perceptible. The experimental TCSs for (CH 3)CHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 39 publications
7
26
1
Order By: Relevance
“…For example at 1 eV the present TCS is a factor of~4 larger than that of Hamada et al and a factor of~3.5 larger that that of Kimura et al [12]. We note that a similar effect was recently reported by Szmytkowski [22] in his measurements of total cross sections for electrons scattering from acetone, when he compared his data to corresponding results from Yamaguchi University [23]. Makochekanwa et al [24] recently demonstrated, using theoretical elastic differential cross sections, that for polar molecules the forward angle scattering corrections at low positron energies could be as large as 67%.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…For example at 1 eV the present TCS is a factor of~4 larger than that of Hamada et al and a factor of~3.5 larger that that of Kimura et al [12]. We note that a similar effect was recently reported by Szmytkowski [22] in his measurements of total cross sections for electrons scattering from acetone, when he compared his data to corresponding results from Yamaguchi University [23]. Makochekanwa et al [24] recently demonstrated, using theoretical elastic differential cross sections, that for polar molecules the forward angle scattering corrections at low positron energies could be as large as 67%.…”
Section: Resultssupporting
confidence: 82%
“…[1][2][3][4][5]]. We therefore do not repeat those details again here, except to note that a tungsten moderator of thickness 1 μm or a nickel moderator of 2 μm was employed in conjunction with a radioactive 22 Na isotope (current activity~2.2 mCi) and some electrostatic optics in order to produce the positron beam. Full details on the comparative performance of these moderators can be found in Zecca et al [13], with consistent TCS results being obtained in either case.…”
Section: Methodsmentioning
confidence: 99%
“…Clearly, both results are subject to considerable systematic uncertainties, but together they should provide a better representation of the true ICS than the uncorrected values. It is thus noteworthy that both are larger than the reported TCS [24] at energies up to 15 eV. Attenuation measurements on strongly polar systems such as acetaldehyde systematically underestimate the TCS, due to the impossibility of discriminating between unscattered electrons and those scattered elastically through small enough an angle to pass through the exit aperture.…”
Section: Resultsmentioning
confidence: 84%
“…Attenuation measurements on strongly polar systems such as acetaldehyde systematically underestimate the TCS, due to the impossibility of discriminating between unscattered electrons and those scattered elastically through small enough an angle to pass through the exit aperture. However, Szmytkowski [24] estimates this systematic effect at only 3% over most of the range shown in Fig. 5 and 5% to 7% below 3 eV, much too small to account for the inconsistency seen in Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation